Evaluation of type 2 Diabetes Mellitus Risk in Patients with post Trauma Splenectomy - Nemati Honar, Behzad; Pishgahi, Mehdi; Forouzanfar, Mohammad Mehdi; Forouzannia, Seyed Ali; Ebadi, Seyed Alireza; Shahrzad, Mohammad Karim (Archives of Men’s Health, 2021)
Introduction: Recent studies suggest that the spleen has an important role as a source of multipotent stem cells and precursors of beta cells of pancreas islets. In addition, increased risk of developing hyperglycemia was reported in patients who underwent splenectomy due to trauma in long-term follow up. Therefore, there might be an association between splenectomy and an increased risk of type 2 diabetes mellitus. In this study, we evaluated the risk of type 2 diabetes and its risk factors including hyperglycemia, dyslipidemia, obesity and hypertension in trauma patients with splenectomy. Materials and methods: In this study, 221 patients who underwent splenectomy surgery due to trauma in the surgical ward of Imam Hossein Hospital 5 to 10 years ago were selected. Those with a history of diabetes, cancer, hyperthyroidism, Cushing’s syndrome, pancreatitis, renal failure, and cirrhosis were excluded from the study. Then fasting plasma glucose, hemoglobin A1c (HbA1c), triglyceride, cholesterol and high density lipoprotein (HDL), body mass index and blood pressure have been evaluated in 90 patients who had had a history of splenectomy due to trauma from 2007, July 23 to 2012, July 22. Results: The results indicate that none of these patients has diabetes, 14.4 percent are in pre-diabetic stage, 56.6 percent has dyslipidemia, 57.7 percent has obesity and 20 percent has hypertension. Conclusion: The results of this study suggest that splenectomy does not increase the risk of type 2 diabetes. Prevalence of diabetes risk factors was approximately the same with those of Tehran population.